Shaped before birth: Obstetric complications identify a more severe clinical phenotype among patients presenting a first affective or non-affective episode of psychosis. (July 2022) - Sagué-Vilavella, Maria; Amoretti, Silvia; Garriga, Marina; Mezquida, Gisela; Williams, Evelyn; Serra-Navarro, Maria; Forte, Maria Florencia; Varo, Cristina; Montejo, Laura; Palacios-Garran, Roberto; Madero, Santiago; Sparacino, Giulio; et al.
Abstract: Obstetric complications (OCs) may contribute to the heterogeneity that characterizes psychiatric illness, particularly the phenotypic presentation of first episode psychoses (FEP). Our aim was to examine the relationship between OCs and socio-demographic, clinical, functioning and neuropsychological characteristics in affective and non-affective FEP. We performed a cross-sectional, study where we recruited participants with FEP between 2011 and 2021, and retrospectively assessed OCs using the Lewis-Murray scale. OCs were used as a dichotomous variable and further stratified into three subtypes: complications of pregnancy, abnormal fetal growth and development, and difficulties in delivery. We performed a logistic stepwise forward regression analysis to examine variables associated with the presence of OCs. Of the 104 participants (67 affective FEP and 37 non-affective FEP), 31.7% (n = 33) had experienced OCs. Subjects with OCs showed a more gradual emergence of prodromal symptoms as well as higher negative and total Positive and Negative Syndrome Scale (PANSS) scores. In the multivariate analysis, the presence of OCs was independently associated with a younger age at first episode of any type (OR = 0.904, p = 0.003) and slower emergence of prodromal symptoms (OR = 0.274, p = 0.011). When considering specific types of OCs, those related with fetal growth were associated with worse neuropsychological performance, while OCs at delivery were related to earlier onset of illness and more severe symptoms. In conclusion, OCs signaled a specific FEP phenotype characterized by earlier and more protracted onset of illness as well as more burdensome symptoms, independently of FEP type (i.e., affective vs non-affective). These results indicate a potential target of early intervention in FEP. Highlights: Perinatal noxious hits point at a worse clinical presentation of psychosis. Progression of prodromes is more gradual when obstetric complications were present. Better perinatal care might be a preventive strategy for negative symptoms.